ISSUES OF EDUCATION OF GIRLS IN A KARAKALPAK FAMILY (TAMADDUN NURI JURNALI, 2024)
The article discusses some of the customs of Karakalpak families when giving birth to a child and raising a girl. In particular, the issue of raising a Karakalpak woman is covered, some traditions of her marriage, as well as the periods of her childhood and adult life, are examined in detail.